Why Should We Talk about Culture, When We Want to Understand ‘Surveillance’? - Kammerer, Dietmar; Justus Liebig University Giessen (My University, 2018)
Why should we talk about culture, when we want to understand surveillance ? The following is a brief sketch towards an answer to this question. It has two parts: first, it presents and discusses how the term culture is used within Surveillance Studies, an emerging transdisciplinary field combining research from social and political sciences as well as cultural studies and the humanities, and highlights the works of Torin Monahan and David Lyon in particular. Second, it puts forward a set of arguments why any reflection on surveillance must not ignore the cultural perspective.
Keywords: David Lyon; humanities; pop culture; surveillance; surveillance studies; ddc:300